PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN PENGUASAAN KONSEP MAHASISWA CALON GURU BIOLOGI - Taufik Samsuri; Herdiyana Fitriani (Bioscientist : Jurnal Ilmiah Biologi, 2016)
Abstract: A research has been conducted to improve the mastery of students of biology teacher candidates through the application of inquiry learning model. This type of research is a classroom action research. This research applied to FPMIPA biology education student of IKIP Mataram, on the subject matter of plant structure and development. The results showed that 91% of students declared complete study on cycles II and 65% of students declared complete in sikus I. Thus the increase in mastery of the concept is in the high category. Based on the results of data analysis can be concluded that biology learning on the subject matter of structure and development of plants with inquiry model can improve the mastery of the concept of biology teacher candidates.